A study on the perspectives of Barangay 60-A, Tacloban City residents on selected NGOs and GOs shelter damage classification schemes - Abarratigue, Cyrene Q.; Caspe, Jay Ryl P.; Dargantes, Arcelyn P.; de Veyra, Geraldine B.; Lim, Ladylyn B. (2014)
This study looks into the perspectives of the Barangay 60-A residents regarding the shelter damage classification schemes used by selected INGOs and GOs. Through an interview schedule, the informants were asked about their perceptions, opinions and knowledge about the classification schemes utilized by selected INGOs and Gos in assessing the shelter damages brought by typhoon Yolanda.
The objectives of this study aim to document the classification schemes or categorical basis used by INGOs and GOs in assessing shelter damages and to analyze the commonalities and differences of the terms used by these INGOs and GOs in categorizing damages. Finally, this study seeks to solicit the views and opinions of Baranagay 60-A residents regarding this classification schemes.
Based on the results of the study, INGOs and GOs possess significant similarities and slight differences. The GOs follow a two-category classification scheme in assessing shelter damages. This is the totally damaged and the partially damaged category. This classification scheme is also followed by OXFAM's shelter program, an INGO which seeks to help the victims of typhoon Yolanda. This organization uses the habitable and unhabitable classification instead of the totally and partially damaged category. CRS on the other hand, follows a three-category classification scheme: Class A- totally destroyed, Class B- requires major repair, and C- requires minor repair.
Most of the informants agree with the classification scheme used by the GOs and INGOs in assessing the damages of their houses. Their issues do not revolve around the categorization but on the distribution of help with regards to housing repair. Other informants suggest that the GOs, specifically the DSWD, should not solely rely on the data given to them by the barangay officials instead they should be the one responsible in conducting the assessment.
Undergraduate thesis (B.A.S.S. Political Science)-- Univeristy of the Philippines, Tacloban.